Leadership Style, Motivation, and Internal Communication Influence PT XYZ Employees Work Effectiveness Via Job Satisfaction - Fitrathul Ihsan; Liswandi Liswandi; Yohanes Joni Pambelum (Jurnal Ekonomi Manajemen Sistem Informasi, 2024)
Every organization or company needs to effectively utilize working time, which means that in a company or institution, time should be used efficiently without wasting any. The objective of this study is to analyze the impact of leadership style, motivation, and internal communication on work effectiveness by means of job satisfaction at the PT XYZ office. This study utilizes a quantitative approach, utilizing primary data sources. A purposive selection strategy was used to choose a sample of 87 employees from PT XYZ. The study's findings indicate that internal communication has the most significant impact on job satisfaction. The leadership style has a substantial positive impact on work effectiveness. This suggests that as the level of leadership style increases, the level of work effectiveness also increases. Motivation does not significantly influence work effectiveness, suggesting that higher levels of motivation do not influence work effectiveness. Internal communication significantly positively impacts work effectiveness. Job satisfaction does not influence work effectiveness, suggesting that higher levels of job satisfaction do not influence work effectiveness. Leadership style significantly influences job satisfaction positively. However, the results differ for motivation, which does not significantly influence job satisfaction. This suggests that higher levels of motivation do not influence job satisfaction.